Multiple stimulated emission fluorescence photoacoustic sensing and spectroscopy - Li, Gaoming (2016)
Multiple stimulated emission fluorescence photoacoustic (MSEF-PA) phenomenon is demonstrated in this letter. Under simultaneous illumination of pumping light and stimulated emission light, the fluorescence emission process is speeded up by the stimulated emission effect. This leads to nonlinear enhancement of photoacoustic signal while the quantity of absorbed photons is more than that of fluorescent molecules illuminated by pumping light. The electronic states' specificity of fluorescent molecular can also be labelled by the MSEF-PA signals, which can potentially be used to obtain fluorescence excitation spectrum in deep scattering tissue with nonlinearly enhanced photoacoustic detection. In this preliminary study, the fluorescence excitation spectrum is reconstructed by MSEF-PA signals through sweeping the wavelength of exciting light, which confirms the theoretical derivation well.